System level modelling of RF power amplifiers based on large-signal measurements - Fager, C.
This paper demonstrates the extraction of three different system level behavioural models of power amplifiers from large signal time domain measurements. The modelling results are evaluated using a common independent CDMA2000SR1 telecommunication input signal. The capability of the models to predict long term memory effects is also evaluated by artificially modifying the bias network in one of the PA prototypes. © 2007 EuMA.